2020
DOI: 10.1108/jd-11-2019-0227
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of documents: information sharing through medical records in healthcare

Abstract: PurposeThe focus of this paper is on the mediating role of medical records in patient care. Their informative, communicative and constitutive facets are analysed on the basis of a case study in an African University teaching hospital.Design/methodology/approachA practice-oriented approach and the concept of boundary objects were adopted to examine medical records as information artefacts. Data from nonparticipant observations and interviews with physicians were triangulated in a qualitative analysis.FindingsTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Patients’ stories, especially their narratives and patient records, formed the boundary objects to make constructive multidisciplinary work possible. A study by Isah and Bystroöm [ 97 ] focused on the role of case notes as mediating artifacts in patient care. Their study demonstrated how case notes were a source of information and an essential, enacting, and mediating part of the work itself.…”
Section: Resultsmentioning
confidence: 99%
“…Patients’ stories, especially their narratives and patient records, formed the boundary objects to make constructive multidisciplinary work possible. A study by Isah and Bystroöm [ 97 ] focused on the role of case notes as mediating artifacts in patient care. Their study demonstrated how case notes were a source of information and an essential, enacting, and mediating part of the work itself.…”
Section: Resultsmentioning
confidence: 99%
“…Doctors themselves have anxiety about writing their notes for care and liability, an anxiety exacerbated by the dawn of the electronic medical record. However, even studies of records' use over time have stuck to treatment in intensive care units or fairly short hospital stays (e.g., Reddy, et al, 2006;Isah and Byström, 2020). The working patient record is not the same as the archival patient record (Fitzpatrick, 2004).…”
Section: For the Recordmentioning
confidence: 99%